FBXL4 deficiency increases mitochondrial removal by autophagy. Issue 7 (11th June 2020) - Alsina, David; Lytovchenko, Oleksandr; Schab, Aleksandra; Atanassov, Ilian; Schober, Florian A; Jiang, Min; Koolmeister, Camilla; Wedell, Anna; Taylor, Robert W; Wredenberg, Anna; Larsson, Nils‐Göran
Abstract: Pathogenic variants in FBXL4 cause a severe encephalopathic syndrome associated with mtDNA depletion and deficient oxidative phosphorylation. To gain further insight into the enigmatic pathophysiology caused by FBXL4 deficiency, we generated homozygous Fbxl4 knockout mice and found that they display a predominant perinatal lethality. Surprisingly, the few surviving animals are apparently normal until the age of 8–12 months when they gradually develop signs of mitochondrial dysfunction and weight loss. One‐year‐old Fbxl4 knockouts show a global reduction in a variety of mitochondrial proteins and mtDNA depletion, whereas lysosomal proteins are upregulated. Fibroblasts from patients with FBXL4 deficiency and human FBXL4 knockout cells also have reduced steady‐state levels of mitochondrial proteins that can be attributed to increased mitochondrial turnover. Inhibition of lysosomal function in these cells reverses the mitochondrial phenotype, whereas proteasomal inhibition has no effect. Taken together, the results we present here show that FBXL4 prevents mitochondrial removal via autophagy and that loss of FBXL4 leads to decreased mitochondrial content and mitochondrial disease. Synopsis: A new Fbxl4 knock‐out mouse model was generated and compared well in terms of disease pathophysiology with findings in patient fibroblasts and a CRISPR/Cas9 knock‐out cell line. Fbxl4 deficiency leads to decreased mitochondrial content leading to a mitochondrial disease. Fbxl4 deficiency increases mitochondrial turnover through the lysosomes. Fbxl4 is involved in mitochondrial quality control. Abstract : A new Fbxl4 knock‐out mouse model was generated and compared well in terms of disease pathophysiology with findings in patient fibroblasts and a CRISPR/Cas9 knock‐out cell line.